2015
DOI: 10.1021/acs.iecr.5b00215
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Melt-Draw Ratio on the Crystalline Structure and Properties of Polypropylene Cast Film and Stretched Microporous Membrane

Abstract: The orientation and crystallization during melt stretching were characterized, and their influence on the lamellar morphology and stretched polypropylene pore structure was clarified. During melt stretching, the MDR range from 40–200 could be divided into two regions. In region I, MDR below 120, the crystalline morphology transformed from ellipsoid spherulites to lamellae structure, and the orientation, elastic recovery, and lamellar lateral dimension were enhanced. The porosity of corresponding stretched micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 51 publications
(90 reference statements)
1
43
0
Order By: Relevance
“…We emphasize the importance of cavitation triggered at large strain as it can be regarded as a signal to predict the ultimate life of the materials upon stretching. Meanwhile, the appearance of voids sometimes is needed in some special fields, for example, creating microporous separation membranes . Understanding the evolution of cavities during the deformation process can provide the possibility of finding an efficient way to promote, restrain, or even heal the cavities.…”
Section: Introductionmentioning
confidence: 99%
“…We emphasize the importance of cavitation triggered at large strain as it can be regarded as a signal to predict the ultimate life of the materials upon stretching. Meanwhile, the appearance of voids sometimes is needed in some special fields, for example, creating microporous separation membranes . Understanding the evolution of cavities during the deformation process can provide the possibility of finding an efficient way to promote, restrain, or even heal the cavities.…”
Section: Introductionmentioning
confidence: 99%
“…2. 22,23,34 To better characterize the crystalline morphology under different DR values, the etched surface morphology of SEM photographs is presented in Fig. According to Daniel 32 and Tao, 33 the most stable TPX crystalline structure of form I could be obtained through cooling from the molten state and is evidenced by the reections at 2q ¼ 9.5 , 13.4 , 16.6 , 18.5 , 20.6 and 21.5 , which belong to peaks not being presented in our results.…”
Section: Resultsmentioning
confidence: 99%
“…14,20 Some papers [21][22][23] reveal that the elongation induced morphology is strongly dependent on the effective stretching ow expressed in terms of the melt draw ratio. A precursor lm with a lamellar morphology is believed to be obtained by crystallization of the chains during melt stretching, which in the literature is called stress induced crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]9,12,13 Some polyolefin membranes have been commercially produced by stretching process, but only patents were filed without any detailed description of the of the fabrication procedure. 2,9,[17][18][19][20][21][22] Subsequently, precursor films go through an annealing process to improve the perfection of crystalline structure in the crystalline region. Many studies have indicated that the polymer molecular structure, i.e., molecular weight (M w ) and molecular weight distribution (MWD), and also processing variables are main factors for this method in controlling the properties of the precursor film and, consequently, the properties of the porous membrane.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]9 It has been reported that annealing changes the nano-scale structure of the precursor films, especially the crystalline structure and enhances the physical properties of semicrystalline polymers by contributing to chain rearrangement. [2][3][4]9,18,19,[22][23][24]27,28 However, a few studies have been reported concerning the formation of microporous membranes from high density polyethylene (HDPE) by dry-stretching. 3,[23][24][25][26] On the other hand, many works focused on the relationship between stretching conditions and properties of finally microporous membranes.…”
Section: Introductionmentioning
confidence: 99%